The Myth of Air Purifier in Mitigating the Transmission Risk of SARS-CoV-2 Virus - Lip Huat Saw; Bey Fen Leo; Chin Yik Lin; Norfilza Mohd Mokhtar; Sawal Hamid Md Ali; Mohd Shahrul Mohd Nadzir (Aerosol and Air Quality Research)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a highly infectious disease that emerged in December of 2019, threatening human health and leading to global public health crises. Airborne transmission via droplets and aerosol has been recently recognized as one of the infection modes for the SARS-CoV-2 virus. Hospitals have deployed/incorporated indoor air purifiers with the hope to minimize the transmission risk of SARS-CoV-2 virus. Nevertheless, the effectiveness of the indoor air purifier in reducing the transmission risk remained unknown. This study uses computational fluid dynamics to model the dispersion of the aerosol particles exhaled from the patient under the influence of an air conditioner, exhaust fans and air purifier. The numerical model showed that airflow from the diffusers, exhaust fans and placement of the air purifier significantly influenced the dispersion pattern of the aerosol particles in the common ward. Multiple air purifiers placed at 1 meter above the floor and next to a patient can increase the total efficiency from 37.14 to 59.91% for weak exhalation and from 36.44% to 48.81% for medium exhalation. No aerosol particles flew out from the door for weak and medium exhalation when multiple air purifiers were deployed in the common ward. Location and matching the clean air delivery rate with the size of the room are the important factors that affect the performance of the air purifier.